Ampicillin Induced Diarrhoea (Journal of Pharmaceutical Negative Results, 2022)
Ampicillin, a type of penicillin, is one the most commonly usedantibiotic which has different indications. It acts as bactericidal or bascteriostatic against different type of organisms. Base on different studies, using antibiotic and ampicillin may accompany with 5 to 30% chance of developing diarrhea. For treating this condition different measures can be taken. Current article is a case report about ampicillin induced diarrhea in a 7 year old male patient who admitted in hospital for viral fever. For managing infection, ampicillin was prescribed but led to diarrhea and physician decided to stopand replaced it with other antibiotic. In this case report, condition in which ampicillin associated diarrhea and its management discussed.